2,3,4,5-Tetrafluorobenzoic acid–4,4′-bipyridine (2/1) - Xiaohui Zhu (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound, 2C7H2F4O2·C10H8N2, contains one molecule of 2,3,4,5-tetrafluorobenzoic acid (tfb) and half of a centrosymmetric 4,4′-bipyridine molecule. Intermolecular O—H...N hydrogen bonds link two tfb molecules and one 4,4′-bipyridine molecule into a trimer. Weak intermolecular C—H...F interactions assemble these trimers into a three-dimensional network structure.